Group theory based at any point - M. A. Albar; S. A. Huq (International Journal of Mathematics and Mathematical Sciences)
If (G,⋅) is a group with identity e, we call G, the group based at e. In this paper, we aim to release the present day group theory which is based at e, by replacing e by an arbitrary element of the group.